ANALISIS PEMANFAATAN E-COMMERCE DAN MEDIA SOSIAL SEBAGAI SISTEM INFORMASI PEMASARAN UNTUK EKSPANSI PASAR UMKM (Studi Kasus UMKM Konveksi Binong Jati, Bandung) - Cahyadi Nurdiansyah; Imam Maliki; Gita Cahyani Lestari (POLITEKNIK PIKSI GANESHA, 2025)
Digital transformation has changed marketing patterns and offers SMEs strategic opportunities to expand their market reach. This study aims to analyze the impact of using e-commerce and social media as marketing information systems on the expansion of the SME market in Bandung City. A quantitative approach is used, using descriptive and verification methods. Data were collected by distributing questionnaires to 40 SME participants and analyzed using multiple linear regression. The results show that the use of e-commerce and social media has a significant impact on the expansion of the SME market. This study concludes that integrating the two digital platforms is key to increasing the competitiveness and growth of SMEs in the digital age.